2001
DOI: 10.1055/s-2001-12217
|View full text |Cite
|
Sign up to set email alerts
|

Cobalamin (Cbl) C/D Deficiency: Clinical, Neurophysiological and Neuroradiologic Findings in 14 Cases

Abstract: The early onset type of cobalamin (Cbl) C/D deficiency is characterised by feeding difficulties, failure to thrive, hypotonia, seizures, microcephaly and developmental delay. It has an unfavourable outcome, often with early death and significant neurological impairment in survivors. While clinical and biochemical features of Cbl C/D deficiency are well known, only a few isolated case reports are available concerning neurophysiological and neuroimaging findings. We carried out clinical, biochemical, neurophysio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
33
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 17 publications
4
33
0
1
Order By: Relevance
“…12,13 On the basis of a number of case reports, brain atrophy is also a pathologic feature in infants with vitamin B 12 deficiency. [14][15][16] Advanced MR imaging-based modalities such as DTI and MR spectroscopy showed abnormalities in a variety of diffuse neurologic disorders, whereas conventional MR imaging findings appeared normal. We hypothesized that patients with clinical symptoms of SACD and biochemical evidence of vitamin B 12 deficiency will have an associated cognitive decline and microstructural alterations in brain WM on DTI, even when conventional MR imaging findings appear normal.…”
mentioning
confidence: 99%
“…12,13 On the basis of a number of case reports, brain atrophy is also a pathologic feature in infants with vitamin B 12 deficiency. [14][15][16] Advanced MR imaging-based modalities such as DTI and MR spectroscopy showed abnormalities in a variety of diffuse neurologic disorders, whereas conventional MR imaging findings appeared normal. We hypothesized that patients with clinical symptoms of SACD and biochemical evidence of vitamin B 12 deficiency will have an associated cognitive decline and microstructural alterations in brain WM on DTI, even when conventional MR imaging findings appear normal.…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that there is a positive correlation between the degree of vitamin B 12 deficiency and abnormality of evoked brain potentials (4,6,18,19). Similarly, in this study, VEP and BAEP tests proved abnormal in 3 and 7 subjects who had serum vitamin B 12 levels of <100 pg/mL, respectively.…”
Section: Discussionmentioning
confidence: 53%
“…Abnormalities of VEP and BAEP developed secondarily to demyelination and axonopathy caused by vitamin B 12 deficiency. The persistence of VEP and BAEP abnormality in the deficiency of vitamin B 12 might be associated with delayed diagnosis of vitamin B 12 deficiency and advanced neurological view (4,6). In a study carried out by Biancheri et al (6), out of 14 cases with congenital cobalamin metabolism disorder, the BAEP results of 9 and the VEP results of 8 cases were determined to be abnormal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, vitamin B 12 deficiency is thought to cause imbalance between the growth factors influencing the central nervous system and neurotoxic cytokines, and increased lactate, glutamate and excitatory amino acids (26)(27)(28). There- (29)(30)(31)(32)(33)(34). We encountered central nervous system signs and symptoms especially in rapidly growing infants in the early period between 2 and 18 months.…”
Section: Discussionmentioning
confidence: 94%